1989
DOI: 10.1073/pnas.86.3.854
|View full text |Cite
|
Sign up to set email alerts
|

Identification of androgen receptors in normal human osteoblast-like cells.

Abstract: The sex steroids, androgens and estrogens, are major regulators of bone metabolism. However, whether these hormones act on bone cells through direct or Androgens and estrogens are major regulators of bone metabolism in males and females, respectively (1). Both hormones interact with growth hormone in control of the adolescent growth spurt (2-4). After growth is completed, androgens and estrogens maintain bone mass in the adult. In women, menopause causes accelerated bone loss that can be prevented by estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
145
1
9

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(161 citation statements)
references
References 28 publications
6
145
1
9
Order By: Relevance
“…In vitro studies reporting the occurrence of androgen receptors (38), androgen metabolism (39) and androgen effects (40) on human osteoblastic cells support this conclusion. A recent study has demonstrated a change in biochemical serum markers of bone metabolism in response to testosterone replacement therapy, suggesting a reduction in bone remodelling (8).…”
Section: European Journal Of Endocrinology (1998) 138supporting
confidence: 72%
“…In vitro studies reporting the occurrence of androgen receptors (38), androgen metabolism (39) and androgen effects (40) on human osteoblastic cells support this conclusion. A recent study has demonstrated a change in biochemical serum markers of bone metabolism in response to testosterone replacement therapy, suggesting a reduction in bone remodelling (8).…”
Section: European Journal Of Endocrinology (1998) 138supporting
confidence: 72%
“…AR expression has been shown in a number of bone cells including pluripotent mesenchymal bone marrow stromal cells, osteoblasts, osteoclasts and osteocytes. (6)(7)(8) Osteoblasts are potential targets for androgen action because they contain a high AR expression. (9)(10)(11) Thus far two osteoblastspecific AR knockouts have been generated.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical evidence of hypogonadism is found in about 20% of men with vertebral fractures [2] and up to 50% of men with hip fractures [3,4], often without other clinical features of gonadal failure. In cell culture studies using human osteoblastlike cells from both men and women [5][6][7], specific androgen receptors can be identified by nuclear and cytosolic binding assays (Table 1). Similarly, osteoblasts obtained from fresh femoral bone specimens can also metabolize the circulating androgen androstenedione to testosterone and 5␣-dihydrotestosterone (DHT) in both men and women [8] at rates dependent mainly on androstenedione concentration.…”
mentioning
confidence: 99%
“…However, estrogen receptors are at least equally abundant in cultures of these cell lines [5,21] and osteoblasts respond metabolically to estrogens in vitro [22] and in fresh biopsy samples of male bone [23]. Aromatase activity is present in cultured osteoblast cell lines [22], demonstrating that these cells have the capacity to convert testosterone to estradiol (and vice versa).…”
mentioning
confidence: 99%